The Handmaid's Tales in Gileadverse : Dynamics of a transmedia storyworld - Machała, Katarzyna (Schöningh and Fink Literature and Culture Studies E-Books Online, Collection 2024., 2024)
In an innovative approach to the world-famous novelist Margaret Atwood and her oeuvre, this book traces the development of the transmedia universe built around Gilead, spanning over two novels, a serial, fan fiction, and social media. It offers a new perspective on 'The Handmaid's Tale' and - by extension - on the dynamics of world building that is difficult, if not altogether impossible, to analyze on the example of larger universes and media franchises. Each chapter offers insight into a different part of the Gilead universe, or a different point of entry, tracing character development, world expansion, the incongruities, and the intricate web of connections between particular elements. The loose threads are tied in 'The Testaments', which is both the grand finale and a springboard for new growth. This book will enable graduate students and scholars of transmedia or Atwood studies to discover new aspects of this storyworld, and to better understand other, larger and more complex ones.